Diagnostic Accuracy of Color Doppler Ultrasound in Detecting Portal Vein Thrombosis in Patients Having Hepatocellular Carcinoma Due to Chronic Hepatitis C Keep Triphasic CT as Gold Standard - Hafeez, Sumyya; Asmat, Faryal; Farooq, Kiran Fatima; Wasim, Sairah; Zubair, Hafsa; Shafqat, Elina (Indus Journal of Bioscience Research, 2025)
Objective: With triphasic CT as the gold standard, the purpose of this study is to ascertain the diagnostic accuracy of color doppler ultrasonography in identifying portal vein thrombosis in patients with hepatocellular carcinoma caused by chronic hepatitis C. Study design: Cross-sectional (validation) study. Settings: Department of Radiology, Fouji Foundation Hospital, Rawalpindi. Duration of study: September 2024 to February 2025. Methodology: The study comprised 334 patients, aged 18 to 60 years presenting with hepatocellular carcinoma due to chronic hepatitis C infection. Prothrombotic disorders such as protein C, S, or factor V deficiency were excluded. 3.5 MHz matched imaging and Doppler frequency transducer was used for Color Doppler US. GE and Philips Health Care’s MDCT scanner 16 detectors were used to perform triphasic CT scans of the abdomen and pelvis. Consultant radiologists performed the color doppler and CT reports. Results: 92.12% color doppler sensitivity, 91.60% specificity, 94.44% PPV, 88.24% NPV, and 91.92% diagnostic accuracy were used to diagnose PVT. Conclusion: Doppler ultrasonography has been shown to have a good diagnostic accuracy in identifying portal vein thrombosis (PVT) in individuals with hepatocellular cancer.